2014
DOI: 10.1248/cpb.c14-00325
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of 5-(3-(Pyrazin-2-yl)benzylidene)thiazolidine-2,4-dione Derivatives as Pan–Pim Kinases Inhibitors

Abstract: Pim kinases play a key role in the regulation of signaling pathways including proliferation, migration, and metabolism and are a potential target for cancer therapy. A series of 5-benzylidenethiazolidine-2,4-diones were synthesized as pim kinase inhibitors. The structure-activity relationships (SAR) of the analogues in inhibiting in vitro pim kinase activity as well as the proliferation of leukemia cell lines were examined. SAR studies indicated that a hydroxyl group at the 2-position of the benzene ring of 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 16 publications
0
16
0
1
Order By: Relevance
“…2,3 -Reaction of thiazolidine-2,4-dione with hydroxybenzaldehydes afforded 5-(hydroxybenzylidene)thiazolidine-2,4-dione compounds. The synthesis of the five 5-(hydroxybenzylidene)thiazolidine-2,4-dione compounds from thiazolidine-2,4-dione and corresponding hydroxybenzaldehydes including 2-hydroxybenzaldehyde, 8,11 5-bromo-2-hydroxybenzaldehyde, 6 3hydroxybenzaldehyde, 5,9 4-hydroxybenzaldehyde 1,3,7,9,11 and 4-hydoxy-3methoxybezaldehyde (vaniline) 7,10,11,12 was reported in the literatures but we have not had information on both physical and spectral properties of the 5-(5-bromo-2-hydroxybenzylidene)thiazolidine-2,4-dione compound which was remarked as (2b) in this report. In this work, the 5-(hydoxybenzylidene)thiazolidine-2,4-dione compounds (2a-e) were synthesized according to the previous publications 5,7,9 and their structures were confirmed by the IR, NMR, MS spectra, as well as by comparing their physical properties and spectral data with those of the similar compounds presented in the literatures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 -Reaction of thiazolidine-2,4-dione with hydroxybenzaldehydes afforded 5-(hydroxybenzylidene)thiazolidine-2,4-dione compounds. The synthesis of the five 5-(hydroxybenzylidene)thiazolidine-2,4-dione compounds from thiazolidine-2,4-dione and corresponding hydroxybenzaldehydes including 2-hydroxybenzaldehyde, 8,11 5-bromo-2-hydroxybenzaldehyde, 6 3hydroxybenzaldehyde, 5,9 4-hydroxybenzaldehyde 1,3,7,9,11 and 4-hydoxy-3methoxybezaldehyde (vaniline) 7,10,11,12 was reported in the literatures but we have not had information on both physical and spectral properties of the 5-(5-bromo-2-hydroxybenzylidene)thiazolidine-2,4-dione compound which was remarked as (2b) in this report. In this work, the 5-(hydoxybenzylidene)thiazolidine-2,4-dione compounds (2a-e) were synthesized according to the previous publications 5,7,9 and their structures were confirmed by the IR, NMR, MS spectra, as well as by comparing their physical properties and spectral data with those of the similar compounds presented in the literatures.…”
Section: Resultsmentioning
confidence: 99%
“…Thiazolidine-2,4-dione (TZD) is an important and attractive heterocyclic system to study properties and applications. In the last time, TZD and some TZDs derivatives were concerned by many scientists all over the world because of their biological activities such as anticancer, 1 antidiabetic, 1,2 antibacterial, 3,4 antioxidant, 3 anti-hyperglycemic 5 or inhibiting Pan-Pim kinases 6 etc.…”
Section: Introductionmentioning
confidence: 99%
“…Previously we reported that a series of compounds, synthesized using indoln-2-one for a scaffold and the imidazole ring for the interaction with the ε-amino group of Lys-67 of PIM-1 kinase, shows PIM kinase inhibitory activities with submicromolar IC 50 values for all PIM-1, PIM-2, and PIM-3 kinases [ 17 ]. It was also found that the introduction of a pyrazine ring substituted with an aminoalkyl moiety, which was expected to make hydrogen bond interactions with PIM kinases, to an appropriate scaffold improved the potency of the compound against PIM kinases [ 18 , 19 ]. Therefore, considering the above three factors, we designed a new series of PIM kinase inhibitors that inhibits PIM kinase by competitively binding to the ATP binding pocket of PIM kinase.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Pim kinases including Pim1, Pim2 and Pim3 are overexpressed not only in hematologic malignancies but also in solid tumors, and have become an attractive targets for therapeutics in cancer. [7][8][9][10] Many Pim kinases inhibitors have been discovered. 11,12 Recently a potent, selective, and orally efficacious pan-Pim kinases inhibitor called CX-6258 has been developed by Cylene Pharmaceuticals, and the IC50 of CX-6258 is 5, 25, and 16 nM for Pim1, Pim2, and Pim3, respectively.…”
mentioning
confidence: 99%